Dampak Kunjungan Masyarakat Terhadap Pendapatan Pedagang di Taman Kota Singaraja Ruang Terbuka Hijau (RTH) Kabupaten Buleleng - Anggara, Ketut Mudi Ari; Indrayani, Luh (Universitas Pendidikan Ganesha, 2025)
This study aims to determine the effect of community visits on the income of traders in the Green Open Space of Singaraja City Park, Buleleng Regency. This study is classified as qualitative research with a case study type. In the data collection process, the author used purposive sampling with the research subjects being traders in Singaraja City Park. Determination of informants began with key informants, namely meatball traders at stall A of Singaraja City Park. Furthermore, it was continued with the snow-ball sampling technique to determine who could be used as further informants and related parties. For related agencies such as Perumda Pasar Buleleng Regency as a medium for describing other information that is worthy of being used as research subjects. Data collection methods used include observation, interviews, and documentation. This study uses qualitative analysis techniques developed by Miles and Huberman, namely data collection, data reduction, data presentation, and drawing conclusions. Testing the validity of the data using source triangulation techniques. This study proves that community visits have a significant impact on traders, uneven visits to each trader are one of the obstacles, such as the same type of merchandise making visitors feel confused, lack of strategy, and location and time of selling which have a crucial impact on each trader.